A Systematic Literature Review of The Role of Ontology in Modeling Knowledge in Software Development Processes - Evi Triandini; Marco Ariano Kristyanto; Ravi Vendra Rishika; Franky Rawung (IPTEK The Journal for Technology and Science, 2021)
Ontology in software development is explained as presenting the properties of things within a domain knowledge and how they are interrelated to each other by defining a set of notions and taxonomies that exemplify the knowledge. It is used to deter- mine the ambiguity in the software requirements specification. Though averred to be useful, the software engineering communities are still unfamiliar with the role of Ontology in modeling knowledge in software development processes. Moreover, not much has been known about the role of Ontology in software engineering processes. The objective is to map and explain the substantiation about the role of Ontology in Modelling Knowledge and the challenge faced by the software engineering team to understand how far ontology can help them determine the ambiguity in model- ing and software development processes. We have carried out a methodical review of the literature issued between 2012 and 2021 and recognized 150 publications that talk over the role of ontology in modeling knowledge in software development pro- cesses. This study conveyed and employed particular inclusion and exclusion criteria in bi-rounds to establish the utmost pertinent publications for our research objec- tive. The review acknowledged 22 applications that explain ontologies’ primary role in software development processes. However, our findings suggest ontology’s role in software engineering as a investigation background requires extra consideration. A further experimental result I needed to better understand the role of ontology in modeling knowledge in software development with quality requirements as well as self-organizing groups.